JENIS KIGO PADA HAIKU KARYA MATSUO BASHO DALAM PERSPEKTIF SEMIOTIK CHARLES SANDERS PEIRCE - Siti Nuraisyah; Nana Rahayu; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Haiku is a Japanese short poem that cannot be separated from its constituent elements, one of which is kigo. Kigo is a key word in haiku which has the meaning of words to symbolize seasons, nature, and time markers. The purpose of this study was to describe the types of kigo found in haiku Matsuo Basho's. This research is a qualitative descriptive study. From the analysis of the data 13 haiku, there are 4 types of classification Kigo is tenmon, seikatsu, doubutsu, and shokubutsu and based on Peirce semiotic analysis found 8 data contains the index and the data it contains symbols 5.Key Words: Haiku, Kigo, Semiotic,Peirce